A Lego snowmobile and the elements of miniaturization. Issue 6 (December 2015) - Davy, Jack
Abstract : Miniature objects are part of our everyday lives, but it is rare that we interrogate them effectively. This article uses a toy Lego snowmobile as an example with which to explore the three technical elements which comprise miniaturization and the ways they can obscure the toy's relationship with the serious contemporary issue of Arctic mineral exploitation.